Synaptic biomarkers in CSF aid in diagnosis, correlate with cognition and predict progression in MCI and Alzheimer's disease. Issue 1 (1st January 2019) - Galasko, Douglas; Xiao, Meifang; Xu, Desheng; Smirnov, Denis; Salmon, David P.; Dewit, Nele; Vanbrabant, Jeroen; Jacobs, Dirk; Vanderstichele, Hugo; Vanmechelen, Eugeen; Worley, Paul
Abstract: Introduction: Amyloid, Tau, and neurodegeneration biomarkers can stage Alzheimer's Disease (AD). Synaptic biomarkers may help track cognition. Methods: In cognitively normal controls, Mild Cognitive Impairment (MCI) and AD, we investigated CSF biomarkers in relation to cognitive measures and as predictors of cognitive and global decline. Results: There were 90 normal controls (mean age 73.0, 58% women), 57 MCI (mean age 74.3, 35% women), and 46 AD (mean age 70.7, 41% women). CSF Aβ1‐42 and Neuronal Pentraxin 2 (NPTX2) were decreased, and CSF Tau, neurogranin, and SNAP25 increased in AD versus controls. Aβ1‐42/Tau or NPTX2/Tau discriminated AD and controls best. NPTX2/Tau correlated strongly with cognition in AD and MCI and predicted a 2–3‐year decline. We replicated findings in the ADNI cohort. Discussion: CSF synaptic biomarkers, particularly NPTX2, which regulates synaptic homeostasis, relate to cognition and predict progression in AD beyond Aβ1‐42 and Tau. This is relevant for prognosis and clinical trials. Highlights: CSF levels of synaptic biomarkers and their ratios to CSF Tau improved AD diagnosis CSF synaptic biomarkers, particularly NPTX2, predicted cognitive decline. Combining CSF biomarkers of neurodegeneration may improve diagnosis or prognosis. NPTX2 relates to interneuron‐dependent circuit homeostasis, likely impaired in AD.